PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMP NEGERI 8 PADANG - Mulyani, Riska; R.,, Syahrul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTThe purpose of this study was categorized into three. First, to describe the text writing skills of the experimental class persuasion students. Second, to describe the text writing skills of the control class students' persuasion. Third, to describe the influence of the cooperative learning which was Think Talk Write (TTW) model assisted by audiovisual media in writing skill related to the persuasive text of class VIII students of SMP Negeri 8 Padang. The type of study was quantitative with quasi-experimental research. The design of this study was static by two groups. The population in this study was VIII grade students of SMP Negeri 8 Padang who were enrolled in 2018/2019 academic year about 252 students. The sample in this study was 64 students that consist of two classes, namely class VIII A as the experimental class and class VIII D as the control class that was taken by using purposive random sampling technique. There were several results of this study. They were: First, persuasive text writing skill of the experimental class students was in the category Very Good (BS) with an average score of 85.94. Second, persuasive text writing skill of control class students was in the category Good (B) with an average score of 76.82. Third, the working hypothesis (H_1) was received at the level of Î± = 0.05 and degrees of freedom (dk) = (n1 + n2) -2 because of tcount>ttable, which is 4.23> 1.70. In other words, the use of model cooperative learning type Think Talk Write assisted by audiovisual media has a significant effect on the persuasive writing skills of class VIII students of SMP Negeri 8 Padang. Therefore, the cooperative learning type Think Talk Write (TTW) model could be used as an alternative in learning persuasive text writing skill at the junior secondary level. Kata kunci:Â Pengaruh, Think Talk WriteÂ , Media Audiovisual, Teks Persuasi